Mechanisms of alveolar type II epithelial cells’ mitochondrial quality control during acute lung injury/acute respiratory distress syndrome: bridging the gap between oxidative stress, inflammation, and fibrosis - Zeng, Lin; Yan, Jiangtian (Frontiers in Physiology, 2025)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are a group of conditions characterized by acute episodes of pulmonary inflammation and increased pulmonary vascular permeability. These conditions often result in severe morbidity and high mortality rates. Increased alveolar-capillary barrier permeability is a pivotal factor in the pathogenesis of ALI/ARDS, and diffuse alveolar epithelial cell (AEC) death is a salient feature of ALI/ARDS. Alveolar epithelium is composed of alveolar type I epithelial cells (AECI) and alveolar type II epithelial cells (AECII), with AECII playing a more critical role. These cells contain a high density of mitochondria in their cytoplasm, and their function depends on mitochondrial quality control (MQC). Existing reviews either focus solely on the mechanisms of AECs and their relationship to lung injury/fibrosis or broadly explore the role of mitochondrial dynamics in lung diseases. However, neither review comprehensively addresses AECII’s MQC and related molecules and signaling pathways. The objective of this study is to investigate the MQC characteristics of AECII in ALI/ARDS, elucidate their role as a regulatory hub for oxidative stress, inflammation, and fibrosis, summarize progress in related clinical trials, and highlight the need for further research to develop effective therapies.